CTX Prophages in Classical Biotype Vibrio cholerae: Functional Phage Genes but Dysfunctional Phage Genomes - Davis, Brigid M. (American Society for Microbiology, 2000)
CTXφ is a filamentous, lysogenic bacteriophage whose genome encodes cholera toxin, the primary virulence factor produced by Vibrio cholerae. CTX prophages in O1 El Tor and O139 strains of V. cholerae are found within arrays of genetically related elements integrated at a single locus within the V. cholerae large chromosome. The prophages of O1 El Tor and O139 strains generally yield infectious CTXφ. In contrast, O1 classical strains of V. cholerae do not produce CTXφ, although they produce cholera toxin and they contain CTX prophages integrated at two sites. We have identified the second site of CTX prophage integration in O1 classical strains and characterized the classical prophage arrays genetically and functionally. The genes of classical prophages encode functional forms of all of the proteins needed for production of CTXφ. Classical CTX prophages are present either as solitary prophages or as arrays of two truncated, fused prophages. RS1, a genetic element that is closely related to CTXφ and is often interspersed with CTX prophages in El Tor strains, was not detected in classical V. cholerae. Our model for CTXφ production predicts that the CTX prophage arrangements in classical strains will not yield extrachromosomal CTX DNA and thus will not yield virions, and our experimental results confirm this prediction. Thus, failure of O1 classical strains of V. cholerae to produce CTXφ is due to overall deficiencies in the structures of the arrays of classical prophages, rather than to mutations affecting individual CTX prophage genes.